Do escudo ao escuto : contribuições da supervisão clínico-institucional para a interface psicanálise e saúde mental em CAPS AD - Albuquerque, Débora Daniele da Rocha (2013)
This work has for objective to investigate the contributions of Supervision Clinic-Institucional for the interface Psychoanalisis and Mental Health in CAPS AD (Psychosocial Care Center for users of Alcohol and Drugs), using, for this point, semi-structured interviews realized with supervisors of CAPS AD from Recife City. Giving place to the supervision not as the the only one either the principal , but as strategic place in the CAPS AD to articulate Clinic and Institution through the Psychoanalitical Ethics, the interviews put in highlights the efects of their practice while identifies impasses and put important questions for cross them and go ahead in this construction. Intervene in the logic necessity of the exception place in the institution was point as structuring condition to build a colective project, sustaining in the horizontal model of the CAPS AD the introduction of differences of the places in the team work. Such cut is the condition to avoid the formation of the two mass between the team work an the user of the institution, for establish an opening to the no-all, which don´t confuse with all-no (Lebrun, 2009). Can do without the exception place by the condition of serving of this is operate effects of a psychoanalitical transmission, assumption of the impossible of the sexual rapport, castration as the engine from the clinic and the continued formation. As a limit and a challenge, the construction of a clinical direction which respect the diversity of the academical formations and has as a north the Psychoanalitical Ethics highlights an work in transference that can sustain the construction of a political project in the colective group, attentive to the psychic function of the drug for the subject, resisting to the segregation of the science speech and de capitalist speech. For beyond the knowledge diferences, there is a know which reside in each one which confronts to the Real of the clinic. On this direction, go out of the complaint to go to the labor demand throught an analist desire, which sustain the psychoanalitical transmission, is crossing the shield (sic) to the listen , change position which situates the Real change to go out of the beautiful soul position for can listening the inconscient subject, listen a body which desire and enjoy.